ENHANCING ORGANIZATIONAL READINESS IN FACING THE ERA OF DISRUPTION WITH RESILIENCE – BASED STRATEGY - Asrunputri, Aisyah Pia; Asidiki, Ubaydah; Dewi, Tiara Sandika (Jurnal Bisnis Terapan, 2024)
This research is intended to identify how the organizational readiness in facing the era of disruption can enhanced, using certain strategies such as resilience- based strategies. Today's organizations are required to be resilient in facing disruption. This disruption gives birth to various risks that must be faced by businesses. Organizations are expanding their perspectives that were once only around operations and finance, now involving human resources. Therefore, it is important for organizations to understand the disruption that affect the organization and their readiness to face these risks. This research uses instruments developed by Deloitte (2023) focusing on measuring the readiness gap trends; ranging from readiness gap in a skill-based approach to readiness gap in leadership in a disrupted world. The sample of this research involving business owners and managers in Indonesia. The results show that majority of the respondents have a significant level of readiness in facing the era of disruption especially in terms of anticipating societal and environmental risk in daily business operation.